Cultural roots of university political radicalism. The case of the patients of the UAS: 1972-1978 - Parra, Sergio Arturo Sánchez (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
This paper analyzes the importance of cultural and ideological factors order that prevailed at the Autonomous University of Sinaloa (UAS) for a group of students known as The Sick of UAS radicalized their political positions and they decided to adopt the armed struggle as a political strategy for taking power in Mexico in the seventies of the twentieth century. Among those elements that caused what we call cultural mutation, we include political pedagogy of university press, the spread of a revolutionary culture sustained by a cluster of discursive productions through instances of the institution itself as Radio UAS, University Bookstore, Editorial and changes to plans and programs of study that helped to politicize the spirits of dozens of young people who assumed that guerrilla violence was the way to transform the society.